Magnetotelluric imaging of anisotropic crust near Fort McMurray, Alberta: implications for engineered geothermal system development - Liddell, M.; Unsworth, M.; Pek, J. (Josef) (Geophysical Journal International, 2016)
Viability for the development of an engineered geothermal system (EGS) in the oilsands region near Fort McMurray, Alberta, is investigated by studying the structure of the Precambrian basement rocks with magnetotellurics (MT). MT data were collected at 94 broad-band stations on two east-west profiles. Apparent resistivity and phase data showed little variation along each profile. The short period MT data detected a 1-D resistivity structure that could be identified as the shallow sedimentary basin underlain by crystalline basement rocks to a depth of 4-5 km. At lower frequencies a strong directional dependence, large phase splits, and regions of out-of-quadrant (OOQ) phase were detected. 2-D isotropic inversions of these data failed to produce a realistic resistivity model. A detailed dimensionality analysis found links between large phase tensor skews (similar to 15A degrees), azimuths, OOQ phases and tensor decomposition strike angles at periods greater than 1 s. Low magnitude induction vectors, as well as uniformity of phase splits and phase tensor character between the northern and southern profiles imply that a 3-D analysis is not necessary or appropriate. Therefore, 2-D anisotropic forward modelling was used to generate a resistivity model to interpret the MT data. The preferred model was based on geological observations of outcropping anisotropic mylonitic basement rocks of the Charles Lake shear zone, 150 km to the north, linked to the study area by aeromagnetic and core sample data. This model fits all four impedance tensor elements with an rms misfit of 2.82 on the southern profile, and 3.3 on the northern